Methods for Quantifying Shrinkage in Latossolos (Ferralsols) and Nitossolos (Nitisols) in Southern Brazil - Silva,Luana da (2017)
ABSTRACT Brown Nitossolos (Nitisols) and Latossolos (Ferralsols), according to the Brazilian System of Soil Classification (SiBCS), have a “caráter retrátil” as their distinctive property. Because this is a new topic, it is necessary to propose methods for evaluation. The objectives of this study were to evaluate methodologies for quantifying the shrinkage of soil using the Syringe Method and the Metallic Mercury Method, and to propose a new one, the “Ring with Sand Method”. Soil samples from eight pedons were used, with six Nitossolos and Latossolos with shrinkage, a Latossolo without shrinkage, and a Vertissolo (Vertissol) with admittedly high shrinkage and expansion. The methods were effective in identifying the greater degree of shrinkage of the Vertissolo . However, the Ring with Sand Method was the only one to indicate significant differences between the Vertissolo and the Latossolo without shrinkage, and this method differentiated the shrinkable soils as to the intensity of the characteristic. The proposed method was effective and can serve as a standard to quantify shrinkage.